The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00246-013-0837-7
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Positive Pressure Ventilation in Critically Ill Children With Cardiac Disease

Abstract: Noninvasive ventilation is effective in respiratory failure from various etiologies. This study aimed to analyze the efficacy of noninvasive positive pressure ventilation (NPPV) in pediatric cardiac patients. NPPV was used (1) as an alternative means of respiratory support in patients with hypoxemic or hypercarbic respiratory failure or with signs of respiratory distress that were considered to require intubation; or (2) as a preventive measure in patients with high risk for extubation failure. Between 2008 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
12
1
1
Order By: Relevance
“…Previous single center studies have shown NIV to be an effective mode of respiratory support in the management of children with heart disease [6], including following cardiac surgery [4, 7, 8]. Our study represents the most comprehensive description to-date of NIV therapy in contemporary pediatric cardiac critical care, and the first to assess NIV therapy in a multi-institutional cohort.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous single center studies have shown NIV to be an effective mode of respiratory support in the management of children with heart disease [6], including following cardiac surgery [4, 7, 8]. Our study represents the most comprehensive description to-date of NIV therapy in contemporary pediatric cardiac critical care, and the first to assess NIV therapy in a multi-institutional cohort.…”
Section: Discussionmentioning
confidence: 96%
“…Previous single-center studies demonstrate the safety and effectiveness of NIV in the management of respiratory insufficiency in infants and children [1-3], including those undergoing cardiac surgery [4-8]. NIV therapy may hold promise to decrease ICU length of stay, complications associated with invasive respiratory support, and improve other clinical outcomes for patients in the CICU by allowing reduction in mechanical ventilation (MV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kovacicova et al [29] performed an observational, prospective, single-center study, including 107 episodes of NIV application in children with cardiac disease: 87% of the episodes occurred after cardiac surgery. Patient mean age was 57 days, with mean weight 4.1 kg.…”
Section: Pediatric Patientsmentioning
confidence: 99%
“…La progresiva incorporación del uso de ventilación no invasiva ha proporcionado una mejoría clínica significativa en los pacientes con falla cardiaca congestiva e hipertensión pulmonar y un probable impacto benéfico en la mortalidad 40 . Finalmente, se ha demostrado en importantes estudios de cohorte que el neonato y niño con SD presenta el mismo 9 o menor riesgo de muerte a corto plazo 41 que el niño sin SD post cardiocirugía.…”
Section: Patología Cardíacaunclassified